Planning for Electricity Access - Chattopadhyay, Debabrata; Kitchlu, Rahul; Jordan, Rhonda L. (2014)
This brief examines planning for access to electricity. That electricity for all campaigns around the globe often fall short of their targets is partly a failure of planning. In the area of generation and transmission, technical changes could improve the handling of key constraints, such as fuel availability, funding, and the rate of building. Planning for distribution networks could be improved by gathering data on end-use demand and deploying geospatial tools. Most important of all, the entire planning process from generation to distribution must be better coordinated if access plans are to be successful.